Analysis of planning and construction solutions of apparatus objects, as factor of influence on the method of determination of their construction periods - Ryabchun, Ya. (Ways to Improve Construction Efficiency, 2019)
The article defines the types of objects of agroindustrial complex and defined aggregated complexes of works for the construction of such objects. The author identified directions for further research to develop an improved method for determining the length of construction based on organizational and technical solutions.